A trial of a self‐assessment tool of problems following treatment of colorectal cancer: a prospective study in Australia primary care. (11th June 2015) - Ngune, I.; Jiwa, M.; McManus, A.; Parsons, R.; Hodder, R.
Abstract : Patients treated for colorectal cancer (CRC) experience considerable physical, social and psychological morbidity. In this study, 66 participants with stages I–III CRC were enrolled in this study. Participants completed the self‐assessment tool for patients (SATp) over a 5‐month period and visited a general practitioner with a copy of their SATp to assist in the management of any problems associated with CRC treatment. General practitioners' notes were reviewed for management actions. Of the 66 participants, 57 visited a general practitioner over the 5‐month study period. A total of 547 problems were identified (median 7; IQR: 3–12.25). Participants with physical problems were more likely to consult their general practitioner (OR: 1.84, CI: 1.05–3.21, P  = 0.03) compared to those with psychological problems. The number of problems experienced by participants did not have any influence on the decision to visit a general practitioner. Psychological problems ( P  < 0.01) significantly reduced over the 5‐month study period. Regular use of the SATp facilitates the identification of long‐term CRC treatment‐related problems. Some of these problems could then be addressed in primary care.